1994
DOI: 10.1029/94gl01714
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional evolution of Kelvin‐Helmholtz billows in stratified compressible flow

Abstract: We present results of an initial study of Kelvin‐Helmholtz instability in a stratified shear flow using a three‐dimensional, nonlinear, compressible, spectral collocation model. The simulation was performed at an intermediate Reynolds number and significantly extends previous studies of homogeneous and stratified shear flows. Our major findings include a secondary instability oriented along the two dimensional velocity field, with counter‐rotating vortices arising due to both buoyancy and shear sources of eddy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
(13 reference statements)
1
20
0
Order By: Relevance
“…For sufficiently inviscid flows, these motions undergo a transition to 3D structure similar to that found in breaking gravity waves, with more recent numerical simulations again consistent with the predictions of linear stability theory (Klaassen and Peltier, 1985;Palmer et al, 1994Palmer et al, , 1996Caulfield and Peltier, 1994;Scinocca, 1995;Fritts et al, 1996b; see also Hill et al, 1999, in this issue). Thus, the initial transitions from laminar, quasi-two-dimensional (2D) to 3D flows are now reasonably understood in sheared and stratified fluids.…”
Section: Introductionsupporting
confidence: 66%
“…For sufficiently inviscid flows, these motions undergo a transition to 3D structure similar to that found in breaking gravity waves, with more recent numerical simulations again consistent with the predictions of linear stability theory (Klaassen and Peltier, 1985;Palmer et al, 1994Palmer et al, , 1996Caulfield and Peltier, 1994;Scinocca, 1995;Fritts et al, 1996b; see also Hill et al, 1999, in this issue). Thus, the initial transitions from laminar, quasi-two-dimensional (2D) to 3D flows are now reasonably understood in sheared and stratified fluids.…”
Section: Introductionsupporting
confidence: 66%
“…Laboratory experiments (Miles 1961;Thorpe 1973a;DaSilva et al 1996) have shown that the transition to turbulence is via the development of 2D Kelvin-Helmholtz (KH) billows that become unstable and eventually breakdown into 3D turbulence. Low Reynolds direct numerical simulations have provided additional insight into the evolution of stratified shear layer turbulence; these include the work of Smyth and Moum (2000), Smyth et al (2001), Joseph et al (2004), Palmer et al (1994Palmer et al ( , 1996, and Werne andFritts (1999, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A best guess here might be that a needed Re turb allowing secondary instability and turbulence for Ri ~0.20 in Event 2 is Re turb ~500 or greater (also depending on Ri ), implying a maximum ν turb / ν ~5. This is because KHI secondary instabilities are increasingly suppressed as Ri increases and Re decreases ([ Klaassen and Peltier , ; Palmer et al ., , ]; also see Figure ). These estimates seem roughly consistent given that we should expect stronger background turbulence when the underlying GW and instability dynamics are more energetic.…”
Section: Discussionmentioning
confidence: 99%